Vimentin intermediate filaments stabilize dynamic microtubules by direct interactions - Laura Schaedel (Nature Portfolio, 2021)
The tasks of the cytoskeleton depend on the fine-tuned interplay between the three filamentous components: actin filaments, microtubules, and intermediate filaments. Here, the authors show in a reconstituted in vitro system that vimentin intermediate filaments stabilize microtubules against depolymerization and support microtubule rescue by direct interactions.